Development of Lightweight Materials for Unmanned Aerial ‎and Micro Aerial Vehicles (UAVs/MAVs)‎ - Patel , Pushplata; Biswas , Debarghya (International Journal of Basic and Applied Sciences, 2025)
Lightweight materials development enhances UAVs and MAVs’ performance and endurance because it improves operational efficiency. ‎UAVs and MAVs are being used more and more in applications like surveillance, search and rescue, and environmental monitoring, which ‎demand strong yet lightweight materials. The lighter the vehicle, the more operation time with more cargo storage and higher operational ‎efficiency. Several researchers are focusing on developing materials that are strong relative to their weight through carbon fiber-reinforced ‎polymers (CFRPs), aluminum alloys, and graphene. These materials strengthen aerial system structures and reduce operational power ‎demand. Several challenges for material development are high production costs and decreased durability in different conditions, while ‎engineers struggle to integrate new materials into advanced UAV and MAV systems. Hybrid material development combines multiple ‎material strengths through combined implementation, while new production processes like additive manufacturing are evolving. This ‎research explores lightweight materials implementation for UAV and MAV applications by considering design aspects and presents barriers ‎and technological advancements in aerial systems‎.